Skills policy in England and Scotland after Leitch - Payne, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2008)
This issues paper examines the emergence of two divergent 'strategic paths' for skills policy in England and Scotland following the recent Leitch Review of Skills. Whereas English policy makers are focused narrowly on boosting skills supply and matching overseas levels of qualification stocks, their Scottish counterparts are increasingly stressing the need for skills to be utilised effectively at work and are looking to integrate skills policy within a wider business improvement, innovation and economic development agenda. This paper looks at the factors that have led Scotland to embark upon a new type of skills strategy and asks whether this may serve to challenge the prevailing policy consensus in England about how to tackle the 'skills problem'.